Effect of Dopant Gas Sources on the Properties of Boron Doped p-a-Si1-xOx:H Films and Their Application to a-Si1-xOx:H Thin Film Solar Cells - Inthisang, Sorapong; Sriprapha, Kobsak (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Hydrogenated amorphous silicon (a-Si:H) thin-film solar cells offer low-cost production and flexibility, making them promising for renewable energy applications. This study examined the effects of the dopant gases diborane (B2H6), trimethyl boron (TMB), and a B2H6 + TMB combination on the optical and electrical properties of boron-doped hydrogenated amorphous silicon oxide (p-a-Si1-xOx:H) films for window layers in a-Si:H solar cells. Films were fabricated using very high frequency plasma-enhanced chemical vapor deposition (VHF-PECVD), optimizing doping concentrations to balance a high optical bandgap (Eopt) and conductivity. TMB-doped films exhibited higher Eopt and better optical properties, while the B2H6 + TMB combination improved conductivity and overall performance. Single-junction a-Si1-xOx:H cells with mixed-doping window layers achieved superior open-circuit voltage (Voc), fill factor (FF), and quantum efficiency (QE) compared to cells doped solely with B2H6 or TMB. These enhancements were attributed to improved interface quality between the window and absorber layers. The findings highlight the advantages of a mixed-doping approach, which optimizes optical and electrical properties, resulting in more efficient and stable thin-film solar cells. This work provides a pathway for developing high-performance and cost-effective photovoltaic devices.